Efficacy of high-frequency rTMS in the treatment of gait disorder and cognition in patients with Parkinson’s disease based on wearable devices and eye-movement assessments - Tang, Hong Yin; Liao, XiangLian; Li, Peng; Zhang, Pengfei; Yao, Jian; Xing, Yilan; Zhao, Xin; He, Xuying; Zan, Jie; Li, Guihua (Frontiers in Aging Neuroscience, 2024)
Postural instability and gait disorder and cognitive dysfunction are common symptoms of Parkinson's disease (PD). Scale assessment is frequently used in the clinic to evaluate PD, but this technique is limited by its lack of sensitivity to changes in disease progression and its difficulty in capturing subtle movements and changes in cognitive function. It is currently believed that high-frequency repetitive transcranial magnetic stimulation (rTMS) can improve motor and cognitive dysfunction in patients with PD, though it remains controversial. Therefore, it is imperative to monitor and dynamically identify changes in postural instability and gait disorder, as well as those in cognitive dysfunction, in PD to develop targeted interventions. In this study, we observed the effect of high-frequency rTMS on gait disorders and cognitive functions in patients with PD by comparing data from wearable devices and eye-tracking devices before and after treatment.